2016
DOI: 10.1111/myc.12577
|View full text |Cite
|
Sign up to set email alerts
|

The role of drug efflux pumps in Malassezia pachydermatis and Malassezia furfur defence against azoles

Abstract: This study aims to evaluate the effect of efflux pump modulators (EPMs) on the minimal inhibitory concentration (MIC) of fluconazole (FLZ) and voriconazole (VOR) in Malassezia furfur and Malassezia pachydermatis. The in vitro efficacy of azoles, in combination with EPMs (ie haloperidol-HAL, promethazine-PTZ and cyclosporine A-CYS), against 21 M. furfur from bloodstream infection patients and 14 M. pachydermatis from the skin of dogs with dermatitis, was assessed using a broth microdilution chequerboard analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 39 publications
1
47
0
3
Order By: Relevance
“…Based on different in vitro tests, some studies have reported high resistance rates for various agents [21][22][23][24]. According to some authors, the appearance of resistant strains would be a concern [25], while a low azole susceptibility of the yeast would be a well-documented phenomenon [26]. Instead, other studies have reported a substantial efficacy against yeastby the antifungal agents of more common use in dogs [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Based on different in vitro tests, some studies have reported high resistance rates for various agents [21][22][23][24]. According to some authors, the appearance of resistant strains would be a concern [25], while a low azole susceptibility of the yeast would be a well-documented phenomenon [26]. Instead, other studies have reported a substantial efficacy against yeastby the antifungal agents of more common use in dogs [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Most M. pachydermatis strains are susceptible to ketoconazole; however, the occurrence of resistant strains has been reported [11,12]. To date, only one study has investigated the mechanisms of azole resistance in M. pachydermatis [13]. The study suggested an involvement of drug efflux pumps [13]; however, it used drug efflux pump inhibitors, not a molecular genetic approach.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only one study has investigated the mechanisms of azole resistance in M. pachydermatis [13]. The study suggested an involvement of drug efflux pumps [13]; however, it used drug efflux pump inhibitors, not a molecular genetic approach.…”
Section: Introductionmentioning
confidence: 99%
“…También existen terapias alternativas coadyuvantes para el tratamiento como es el uso de Oxitiamina para el tratamiento superficial de las micosis, especialmente las causadas por la especie M. pachydermatis, ya que demostró ser particularmente sensible. [12,13,22] Identificar específicamente el agente causal de las diferentes infecciones micóticas nos permite conocer mejor su epidemiología, distribución geográfica y patogenia, así como también la elección de los antifúngicos para un tratamiento adecuado. [1,2,9,10,11,13,14,15,16,17].…”
Section: Discussionunclassified